The Role of Household Flooring on Childhood Diarrhea Among Children 0 to 23 Months of Age in Ethiopia: A Nationally Representative Cross-Sectional Study Using a Multi-Level Mixed Effect Analysis - Biniyam Sahiledengle; Abera Kumie; Daniel Atlaw; Yohannes Tekalegn; Demelash Woldeyohannes; Demisu Zenbaba; Tadesse Awoke (SAGE Publishing, 2021)
Introduction: Household flooring has been associated with diarrhea, but few studies have examined the association between childhood diarrhea and type of household flooring considering the individual and community level characteristics. We aimed to determine if household flooring was associated with childhood diarrhea among children 0 to 23 months of age in Ethiopia. Methods: Data from the fourth round of the Ethiopian Demographic and Health Survey (EDHS) conducted in 2016 is used to carry out the analysis. The EDHS was large, cross-sectional by design and nationally representative. In the current analysis, we included children 0 to 23 months of age (n = 4552) with their mother and 636 community clusters. To get information about the occurrence of diarrhea, mothers/caregivers were asked, "Has (NAME) had diarrhea in the last 2 weeks?" The response to this question was recorded as, "yes" or "no." A multilevel binary logistic regression model was fitted to identify factors associated with childhood diarrhea. Results: The overall prevalence of diarrhea among children 0 to 23 months of age in Ethiopia was 15.5% (95% CI [confidence interval] 14.4-16.5). No association was found between childhood diarrhea and type of household flooring (adjusted odds ratio [AOR] 1.05, 95% CI 0.59-1.88). The adjusted odds also showed that the age of the child, having an acute respiratory infection (ARI), and size of the child at birth were associated with diarrhea. Conclusion: We found no association between childhood diarrhea and the type of household flooring. Further research with strong research design is needed to determine the effect of household flooring on childhood diarrhea.